2011
DOI: 10.1155/2011/245181
|View full text |Cite
|
Sign up to set email alerts
|

Detection of N-Glycolyl GM3 Ganglioside in Neuroectodermal Tumors by Immunohistochemistry: An Attractive Vaccine Target for Aggressive Pediatric Cancer

Abstract: The N-glycolylated ganglioside NeuGc-GM3 has been described in solid tumors such as breast carcinoma, nonsmall cell lung cancer, and melanoma, but is usually not detected in normal human cells. Our aim was to evaluate the presence of NeuGc-GM3 in pediatric neuroectodermal tumors by immunohistochemistry. Twenty-seven archival cases of neuroblastoma and Ewing sarcoma family of tumors (ESFT) were analyzed. Formalin-fixed, paraffin-embedded tumor samples were cut into 5 μm sections. The monoclonal antibody 14F7, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…Aberrant expression of carbohydrate structures in cancer, including GSLs, has been known for decades (61,62), and GSLs in tumor cells have been shown to change their structure and organization in the membrane to promote tumor progression (60). In addition to GSLs indicated to be associated with CSCs in this study, the following were found to be highly expressed in human cancer but either absent or present in negligible amounts in normal cells/tissues: (i) blood group A-like antigens expressed in tumor cells of blood group O or B patients [the structure is GalNAcα1-O-Ser/Thr, termed Tn (63)(64)(65); (ii) sialyl 2-6Tn antigen [i.e., NeuAcα2-6GalNAcα1-O-Ser/Thr (66)]; and (iii) extended type-I antigen [i.e., Le a on Le a (67) or Le b on Le a (68,69)].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of carbohydrate structures in cancer, including GSLs, has been known for decades (61,62), and GSLs in tumor cells have been shown to change their structure and organization in the membrane to promote tumor progression (60). In addition to GSLs indicated to be associated with CSCs in this study, the following were found to be highly expressed in human cancer but either absent or present in negligible amounts in normal cells/tissues: (i) blood group A-like antigens expressed in tumor cells of blood group O or B patients [the structure is GalNAcα1-O-Ser/Thr, termed Tn (63)(64)(65); (ii) sialyl 2-6Tn antigen [i.e., NeuAcα2-6GalNAcα1-O-Ser/Thr (66)]; and (iii) extended type-I antigen [i.e., Le a on Le a (67) or Le b on Le a (68,69)].…”
Section: Discussionmentioning
confidence: 99%
“…With this score, we could classify tumours in positive and negative for the expression of NeuGc-GM3. Positive tumours were considered when the score value was at or above 5 that was the cut-off, being negatives those under this value (Scursoni et al 2011). …”
Section: Immunohistochemical Evaluationmentioning
confidence: 99%
“…This variant contains glycolylated sialic acid, which is not detected in normal human tissues and fluids, including the healthy retina (Higashi et al 1988;Marquina et al 1996;Scursoni et al 2010Scursoni et al , 2011Blanco et al 2011Blanco et al , 2012Blanco et al , 2013Zhong et al 2012;Lahera et al 2014). Human cells lack of the enzyme cytidine monophospho-N-acetylneuraminic acid hydroxylase, which regulates its synthesis (Irie & Suzuki 1998;Malykh et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations